The hide and seek of Plasmodium vivax in West Afr"ca: report from a large-sca e study in Beninese asymptomatic 5 bjects.. - Poirier, Philippe; Doderer-Lang, Cecile; ATCHADE, SOSSA PASCAL; Lemoine, Jean Phillipe; Coquelin de l'Isle, Marie-Louise; BIGOT, KOFFI ANDRÉ; Abou-bacar, Ahmed; Pfaff, Alexander W.; Brunet, Julie; Arnoux, Lydia; Haar, Elodie; Filisetti, Denis (My University, 2016)
Background: Plosmodium vivox is considered to be absent from western Africa, where the prevalence of Duffy-negative red blood cell phenotype proves to be high. Several studies have, however, detected Pvivox infection cases in This part of Africa, raising the question of what is the actual prevalence of P vivox in local populations. Methods: The presence of P vivox was investigated in a large population of healthy blood donors in Benin using microscopy, serology and molecular detection. The seroprevalence was measured with species-specific ELISA using two recombinant P vivox proteins, namely rPvMSPl and rPvCSP1. Specific molecular diagnosis of P vivox infection vvas carricd out using nested-PCR The performances and cut-off values of both rPvCSP1 and rPvMSP1 ELISA were first assessed using sera from P vivax-infected patients and from non-exposed subJects. Results~ Among 1234 Beninese blood donors, no parasites were deteeted when using microscopy, whereas 28.7% (354/~ :234) of patients exhibited had antibodies against rPvMSP1, 21.6% (266/1234) against rPvCSP1, and 152% (187/1234) against both. Eighty-four sarnples were selected for nested-PCR analyses, of which 13 were positive for P vivax nested-PCR and ail Duffy negative. Conclusion: The results of the present study highlight an unexpectedly high exposure of Beninese subjects to P vivox, res dring in sub-microscopic infections. This suggesrs a probably underestirnated and insidious parasite presence in western Africa While the vaccination campaigns and therapeutic efforts are ail focused on Plosmodium folciporum, it is also essential to consider the epidemiological irnpact of P vivax.
Keywords: Plasmodium vivox; Malaria; [LISA; MSP1; CSPl; Western Africa; Benin; Blood donors